Residential Proximity to Major Roadways Is Associated With Increased Levels of AC133+ Circulating Angiogenic Cells. Issue 11 (November 2015) - DeJarnett, Natasha; Yeager, Ray; Conklin, Daniel J.; Lee, Jongmin; O'Toole, Timothy E.; McCracken, James; Abplanalp, Wes; Srivastava, Sanjay; Riggs, Daniel W.; Hamzeh, Ihab; Wagner, Stephen; Chugh, Atul; et al.
Abstract : Objectives—: Previous studies have shown that residential proximity to a roadway is associated with increased cardiovascular disease risk. Yet, the nature of this association remains unclear, and its effect on individual cardiovascular disease risk factors has not been assessed. The objective of this study was to determine whether residential proximity to roadways influences systemic inflammation and the levels of circulating angiogenic cells. Approach and Results—: In a cross-sectional study, cardiovascular disease risk factors, blood levels of C-reactive protein, and 15 antigenically defined circulating angiogenic cell populations were measured in participants (n=316) with moderate-to-high cardiovascular disease risk. Attributes of roadways surrounding residential locations were assessed using geographic information systems. Associations between road proximity and cardiovascular indices were analyzed using generalized linear models. Close proximity (<50 m) to a major roadway was associated with lower income and higher rates of smoking but not C-reactive protein levels. After adjustment for potential confounders, the levels of circulating angiogenic cells in peripheral blood were significantly elevated in people living in close proximity to a major roadway (CD31 + /AC133 +, AC133 +, CD34 + /AC133 +, and CD34 + /45 dim /AC133 + cells) and positively associated with road segment distance (CD31 + /AC133 +, AC133 +, and CD34 + /AC133 + cells), traffic intensity (CD31 + /AC133 + and AC133 + cells), and distance-weighted traffic intensity (CD31 + /34 + /45 + /AC133 + cells). Conclusions—: Living close to a major roadway is associated with elevated levels of circulating cells positive for the early stem marker AC133 + . This may reflect an increased need for vascular repair. Levels of these cells in peripheral blood may be a sensitive index of cardiovascular injury because of residential proximity to roadways. Abstract : Supplemental Digital Content is available in the text.